Effect of partial discharges on thermal breakdown of oil‐impregnated paper. (14th October 2015) - Niasar, Mohamad Ghaffarian; Kiiza, Respicius Clemence; Taylor, Nathaniel; Edin, Hans
Abstract : In this paper, we investigate the effect of partial discharges (PDs) on the thermal breakdown voltage of oil‐impregnated paper (OIP). A disk‐shaped cavity in a stack of paper sheets formed the PD source. The paper sample was exposed to PDs for 18 h. Dielectric spectroscopy measurements were performed on the samples before and after exposure to PD activity. The dielectric spectroscopy results showed a big change in the real and imaginary part of the permittivity. These results were used to calculate the activation energy and heat losses inside the insulation. In order to investigate the possibility of thermal breakdown in the system, the OIP system was simulated by using the FEM software COMSOL Multiphysics. The heat produced by PD pulses and dielectric losses was considered in the simulation. The results show that for the OIP insulation, PD activity can reduce the thermal breakdown voltage by a factor up to 4 times. © 2015 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.